Medidas de bioseguridad en servidores de recojo de residuos sólidos y su relación con el factor riesgo laboral Iquitos 2020 - Bernuy Gómez, Amalia Rosa (2022)
This research work shows a small part of the universe of deficiencies in biosafety measures that solid waste collection workers of the provincial municipality of Maynas experience day by day during their collection. This work has had an execution period of 6 months. The objective of this is to determine the bio-safety measures in the solid waste collection servers of the Provincial Municipality of Maynas and relate it directly to the occupational risk factor 2020. The research methodology is based on a quantitative approach of the relationship level -correlational, the population under study was made up of all the workers of the Provincial Municipality of Maynas, which made a total of 55, which coincided with the sample, from the results found it is clear that biosecurity measures are directly related to the risk factor labor affirmation valid with 99% reliability, it was also found that the probability of finding a specific risk, option few is 0.03384 and the probability of finding an anatomical physical risk, option few times is 0.366